Bioequivalence study of voriconazole for intravenous infusion in healthy Chinese subjects under fasting conditions - Xiang, Zhangqiang; Li, Mupeng; Cui, Shaoting; Gan, Chunyan; Liu, Fangfang; Huang, Qian; Mai, Gang; Fan, Lianlian (Journal of pharmaceutical sciences, 2025)
Voriconazole, a second-generation triazole, is used to prevent and treat invasive fungal infections. This study aimed to assess the bioequivalence and safety of test and reference voriconazole intravenous infusion under the fasting conditions. The study employed a randomized, open-label, single-dose, two-period, crossover trial design. Eligible subjects randomly assigned for screening, receiving either the test or reference voriconazole for intravenous infusion during the first period, with alternative products administered during the second period. The washout period lasted 7 days. The single administration dosage was fixed at 6 mg/kg. Nineteen blood samples were collected at pre-dose and up to 46 h post-dose for each subject. The validated LC-MS/MS method was used to determine the concentration of voriconazole in plasma. Twenty-four subjects were enrolled in the study, comprising 20 males and 4 females. The primary pharmacokinetic parameters (mean ± SD) were as follows: C was 4631.20 ± 744.80 and 5008.09 ± 1020.77 ng/mL, AUC was 27,121.07 ± 12,658.03 and 28,674.08 ± 13,118.05 ng*h/mL, and AUC was 28,056.10 ± 14,428.76 and 29,616.29 ± 14,783.70 ng*h/mL for the test and reference formulations, respectively. The 90 % confidence intervals of geometric mean ratios for C , AUC , and AUC fell within the range of 80.00 % to 125.00 %. Both products were well tolerated and no serious adverse event was observed. The test and reference voriconazole intravenous infusion demonstrated bioequivalence and good tolerability.